ANALISIS PENGARUH PENGGUNAAN ABU SABUT KELAPA SEBAGAI FILLER PADA CAMPURAN ASPAL RETONA BLEND - Meylis Safriani; Dian Febrianti (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2016)
Transport infrastructure is one element of the regional development is indispensable for the smooth access to the existing facilities in the region. The material used in the construction of highways, among others, aggregates, asphalt and filler. During this time the filler material that is often used in asphalt mixtures are cement, lime, stone dust, fly ash. However, these filler materials inventory is limited and relatively expensive. Accordingly, the need to find alternative cheap and easily obtained. One alternative is the utilization of local natural resources. The ash of coconut fiber can not be used anymore and are usually thrown away by society. By using the principles of reuse, recycle and recovery, coconut husk ash is expected to be recovered thus reducing the waste bin. The purpose of this study was to determine the effect of the use of coconut husk ash as filler to mix asphalt Retona Blend 55 and to find out the coconut husk ash can be used as a substitute for the filler material mixture highway or not. The method in this study using laboratory experiments. The research showed that most of the physical properties meet the requirements prescribed specifications. Examination of the physical nature of asphalt Retona Blend 55 which includes examination density, penetration, ductility, and the softening point indicates that the asphalt can be used for fulfilling the requirements set. The composition of the mixture that the best results are with the composition of the mixture by using coconut husk ash as filler by 4.5% with the optimum asphalt at 6.25%. The use of optimum asphalt of 6.25% resulted in a value of 1295.47 kg stability, flow plastically 4.0 mm, MQ 328.51 kg, density of 2.21 g / cm3, VIM 5.43%, 17.89% VMA, VFB 70.17%. Those values have been in accordance with the standard specifications of the Department of Public Works.Keywords: filler, coconut husk ash, Retona Blend 55, mixture of asphalt